2006
DOI: 10.1007/s00284-005-0180-1
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Dibenzofuran by Janibacter terrae Strain XJ-1

Abstract: Abstract. The dibenzofuran (DF)-degrading bacterium, Janibacter terrae strain XJ-1, was isolated from sediment from East Lake in Wuhan, China. This strain grows aerobically on DF as the sole source of carbon and energy; it has a doubling time of 12 hours at 30°C; and it almost completely degraded 100 mg/L )1 DF in 5 days, producing 2,2¢,3-trihydroxybiphenyl, salicylic acid, gentisic acid, and other metabolites. The dbdA (DF dioxygenase) gene cluster in the strain is almost identical to that on a large plasmid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 35 publications
(32 reference statements)
0
12
0
Order By: Relevance
“…Janibacter marinus had no other report except its 16S partial sequence record in GenBank. According to previous study, the genus Janibacter has the ability of degrading fluorene, diphenyl ether, carbazole, dibenzo-p-dioxin [47], anthracene, phenanthrene [48], mono-chlorinated dibenzo-p-dioxins [49], dibenzofuran [48,50], and polychlorinated biphenyls (Aroclor 1242) [51]. The aim of the present work was to isolate and characterize a PAHdegrading bacterium, J. anophelis strain JY11 from contaminated environmental samples, and to evaluate its PAHs-degradation potential.…”
mentioning
confidence: 99%
“…Janibacter marinus had no other report except its 16S partial sequence record in GenBank. According to previous study, the genus Janibacter has the ability of degrading fluorene, diphenyl ether, carbazole, dibenzo-p-dioxin [47], anthracene, phenanthrene [48], mono-chlorinated dibenzo-p-dioxins [49], dibenzofuran [48,50], and polychlorinated biphenyls (Aroclor 1242) [51]. The aim of the present work was to isolate and characterize a PAHdegrading bacterium, J. anophelis strain JY11 from contaminated environmental samples, and to evaluate its PAHs-degradation potential.…”
mentioning
confidence: 99%
“…Primary sequence analysis of these dioxygenases shows that amino acid residues responsible for active-site metal binding are strongly conserved, which is further supported by structural studies on a subset of these enzymes. One of the common peptide folds of dioxygenases is called a bicupin structure, which is characterized by two homologous b-barrel (cupin) domains in each subunit (Jin et al 2006). A functional cupin domain is characterized by two highly conservative sequence motifs of G(X) 5 HXH(X) 3,4 E(X) 6 G and G(X) 5 PXG(X) 2 H(X) 3 N (Dunwell et al 2001).…”
mentioning
confidence: 99%
“…Jin et al . () has reported that the location of ‘DF‐degrading genes’ dispersed not only in chromosomal but also extrachromosomal DNA, like bacterial plasmid. It could be a good approach to explain the DF‐degrading activity of strain PH‐08 in both angular and lateral dioxygenation.…”
Section: Resultsmentioning
confidence: 99%